Análisis fenológico en pastizales de dehesa (Pastos, 1980)
One oí the features of the dynamics of the grazing-lands is represented by its evolution during primary growth, when all phenological sings of the plants are seen. In the «dehesa» área in Salamanca, the prevernal, vernal and aestival periods are the most significant, and show the highest quantity of differentiatingpoints between one typegrazing-land and another. It was during these periods that regular observadons were made in 21 allotments, which belong to the most representative communities in the área, showing for each of the species its phenological state at any given moment. The information gathered has been simplified so as to offer a more general view of the phenological aspects of each type of grazing-land, summarizing the observations made per species for the group of pastures of similar taxonomic category. Likewise, the species which showed phisionomical character were selected, i.e.: those which contribute in highest proportion to the biomass of the community; in a word, those species which are dominant due to their hi^her absolute frecuency or their greater covering. To-complement this, the characteristic species are also considered. This study, descriptive in its essence, enables us on the one hand, to correlate the specific phenological observations with the general characteristics of the grazing-land to which they belong, and, in the other, to analyse the evolution of the same species in different pastures. The results obtained are given graphically, showing the differences between the definable types of pasture using the oligotrophy-eutrophy gradient

Distribución de la vegetación en una ladera sometida a riego temporal (Pastos, 1976)
A quantitative analysis of the vegetation on a slope of a "dehesa" of Salamanca pro- vince has been made for the purposes of observing the effects of temporal irrigation. The 17 samples takings that were made included the presence of a total of 102 species whose abundance was studied by means of the analysis of correspondances. The first 3 components, which cover 47,21 % of the variance, are deduced and are interpreted from the analysis; the first as reflecting the access to water, the second as representative of the retention of water. The third seems to be related to the similarity between samplings. In the plañe defined by the first and second components, three zones became apparent; these were identified as swamping, aridity and an intermediate zone between these two. This intermediate zone is formed in the vértex of the directions of the other two which may be schematically represented as two linear trajectories which have the form of lines regres- sion and of which the coefficient of correlation are significantly different of zero. PASTOS